Patient adherence to an exercise program for chronic low back pain measured by patient-report, physiotherapist-perception and observational data. (2nd December 2019) - Peek, Kerry; Carey, Mariko; Mackenzie, Lisa; Sanson-Fisher, Robert
ABSTRACT: The effectiveness of exercise programs for chronic low back pain (CLBP) is dependent upon patient adherence which is problematic to measure accurately. This cross-sectional observational study aimed to compare patient-reported levels of adherence with physiotherapists' perceptions of patient adherence; and to explore the proportion of patients who could accurately recall and demonstrate the exercises contained within their prescribed exercise program for CLBP. Participating patients ( n = 61) included those attending for a follow-up consultation with a physiotherapist ( n = 15) at a consenting practice ( n = 6) who had been prescribed an exercise program for CLBP. Patients were asked to self-report their level of adherence to the exercise program which was then compared to their physiotherapist's perception of adherence. Patients were also asked to recall and demonstrate the exercise program to an independent researcher, which was compared to the prescribed program. Results indicated that in total, 24 patients (39%; 95% CI: 27–52%) self-reported as being completely adherent compared with 10 patients (16%; 95% CI: 8–28%) who were perceived by their physiotherapists as completely adherent (raw agreement: 0.21). However, only nine patients (15%, 95% CI: 7–26%) were able to accurately recall and demonstrate their prescribed exercise program to the researcher, of which eight of these nine patients self-reported complete adherence to the exercise program. In comparison, only four of these nine patients were perceived by the physiotherapist to be completely adherent. These results suggest that patient adherence to home-based exercise programs for CLBP might be assessed more accurately using multi-faceted measures which include an observational component.